Singlet scalars as dark matter and the muon (g − 2) anomaly - Bastián Díaz Sáez (Elsevier, 2021)
We explore a simple model containing two singlet scalars as dark matter candidates and a vector-like lepton. Evading collider and dark matter constraints, the model is able to accommodate the correct dark matter relic abundance and the (g−2)μ anomaly when the masses of the three new fields are around 100 GeV and the values of the minimum amount of required couplings are order one.